Normative values of the vibration perception thresholds at finger pulps and metatarsal heads in healthy adults. - Linnéa Ekman; Eero Lindholm; Elisabeth Brogren; Lars B Dahlin (PLoS ONE, 2021)
Aims To establish normative values of vibration perception thresholds (VPTs), using multi-frequency vibrometry at finger pulps and at metatarsal heads of the foot in healthy adults. We also aimed to investigate factors that could potentially affect VPTs such as age, sex, height, weight, foot- or handedness and skin temperature. Methods VPTs were examined in 924 healthy and randomly selected subjects in the southern Sweden (mean 46 years; 628 women and 296 men). Inclusion criterias were adult subjects (>18 years) in considerable health without diabetes mellitus or other nerve affecting disorders. VPTs were measured at the finger pulps of index and little finger, as well as the first and fifth metatarsal heads of the foot, through multi-frequency vibrometry using the VibroSense Meter® I device. Patient characteristics were recorded and skin temperature was measured before assessment of VPTs. Results We present normative values of VPTs for a large population of both male and female subjects in various ages. VPTs detoriated as age increased (0.09-0.59 dB per year; p<0.001), i.e. progressing with normal aging. Increasing skin temperature affected VPTs in finger pulps, but not at metatarsal heads, with -0.2 to -1.6 dB, i.e. vibration perception improved with higher temperatures. Height was only found to affect the VPTs of metatarsal heads (250 Hz: 0.42 dB per cm). Sex, weight and handedness did not affect the VPTs. Conclusion We investigated the normative values of VPTs and presented affecting factors as age, skin temperature and height. With these results, VPT testing through multi-frequency vibrometry is enabled to be used in a clinical practice as a diagnostic tool when investigating neuropathy and other neurological disorders.